GAMBARAN MOTIVASI IBU DALAM PEMBERIAN ASI EKSKLUSIF DI DESA TUNGGULWULUNG KEC. PANDAAN KAB. PASURUAN - Mardiyana, Rina; Wati, Sinta (JURNAL KEPERAWATAN SEHAT, 2016)
Breastfeeding It is the best food for babies. Exclusive breastfeeding, the first 6 months of a babys birth, can meet the needs of the baby, for growth and development. However, until recently, exclusive breastfeeding, still got a response that is not good. Low awareness, and no encouragement or motivation of the mother, in exclusive breastfeeding, which makes exclusive breastfeeding is still low. So many benefits and advantages to breastfeeding, for the mother and baby. This study aims to, know the motivation of mothers in exclusive breastfeeding. The design of this research, descriptive research. Using sampling techniques, sampling nonprobability, with the type of purposive sampling. Population in the capture is, mothers with babies 7-9 months uisa, in the Tunggulwulung village, District Pandaan, Pasuruan, totaling 35 people. Sampling using purposive sampling techniques, and found 25 samples. Data taken with questionnaires by respondents. Data sources using primary data, from the distribution of questionnaires to mothers. After the data collected is done data processing, through the editing stage, codimg, scoring, tabulating and followed by calculation using the T-score, based on a Likert scale. The results showed that most mothers had low motivation, as many as 20 people (80%). Low motivation resulting from other factors, such as lack of knowing the benefits and superiority of breastfeeding, and the absence of encouragement or motivation on the mother to give exclusive breastfeedingKeywords: Breastfeeding, Motivation, exclusive breastfeeding